KEPASTIAN DASAR HUKUM PEMIDANAAN PELAKU PENIMBUN OBAT COVID-19 DI INDONESIA - Deren Adi Chandra; R. Rahaditya (Jurnal Hukum Adigama, 2022)
The Covid-19 virus spread so widely that it was declared a pandemic in Indonesia, thus increasing the need for Covid-19 drugs when the Covid-19 drug was scarce on the market, it became difficult for people who needed the Covid-19 drug to cause drug prices to soar . This is used as an opportunity to buy drugs and make drug prices soar. The research method used is normative juridical research. The results of this study are that the Indonesian government has made efforts to create legal certainty for unscrupulous business actors who are not responsible because they have hoarded Covid-19 drugs which can already be classified as important items during a pandemic emergency, namely with the sanctions contained in the Trade Law, specifically in Article 107 juncto Article 29 paragraph (1). In an effort to overcome the hoarding of Covid-19 drugs, in addition to establishing laws and regulations related to the crime of hoarding, the Government of Indonesia has also issued a policy regarding the implementation of HET for several drugs intended for Covid-19 sufferers. In addition, the government is also cooperating with law enforcement officials in taking action against drug hoarders.